Mathematical study of nanotechnology in drug delivery - Wang, Lei. (2008)
Recently, an intensive use of nanotechnology exists in the medical field for drug delivery and biotechnology with promising and significant successes. The nature of drug delivery is multi-disciplinary and bio-engineering can offer an important impact. This study is to understand implant drug delivery, inhalation drug delivery, and porous polymer microcarriers and controlled, sustained release. The non-invasive inhalation approach can lead to rapid on seto faction and good bio-availability.